2016
DOI: 10.1007/s13361-016-1452-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aggregation Propensity of a Human Fc-Fusion Protein Therapeutic by Hydrogen/Deuterium Exchange Mass Spectrometry

Abstract: Abstract. Aggregation of protein therapeutics has long been a concern across different stages of manufacturing processes in the biopharmaceutical industry. It is often indicative of aberrant protein therapeutic higher-order structure. In this study, the aggregation propensity of a human Fc-fusion protein therapeutic was characterized. Hydrogen/deuterium exchange mass spectrometry (HDX-MS) was applied to examine the conformational dynamics of dimers collected from a bioreactor. HDX-MS data combined with spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…These data suggest that the autophagy‐lysosome pathway, involved in the intracellular protein quality control by removing large misfolded proteins and proteins aggregates, is activated in liver cells expressing hFIX‐Fc fusion proteins . This hypothesis is in accordance with the propensity of Fc fusion proteins to form protein aggregates, which is mostly induced by hydrophobic interactions . Indeed, it has been shown that the coupling of the Fc region to the hFIX resulted in a difference in hydrogen atom exposition of residues 408‐414, which potentially favoured hydrophobic interactions and subsequent formation of hFIX‐Fc fusion protein aggregates.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These data suggest that the autophagy‐lysosome pathway, involved in the intracellular protein quality control by removing large misfolded proteins and proteins aggregates, is activated in liver cells expressing hFIX‐Fc fusion proteins . This hypothesis is in accordance with the propensity of Fc fusion proteins to form protein aggregates, which is mostly induced by hydrophobic interactions . Indeed, it has been shown that the coupling of the Fc region to the hFIX resulted in a difference in hydrogen atom exposition of residues 408‐414, which potentially favoured hydrophobic interactions and subsequent formation of hFIX‐Fc fusion protein aggregates.…”
Section: Discussionmentioning
confidence: 58%
“…Studies with NH 4 Cl, which inhibits the autophagic flux into lysosomes, led to hFIX‐Fc proteins be redirected from the lysosomal compartment to organelles such as endosome with a quicker degradation rate, or increased the level of misfolded hFIX‐Fc protein within the cell resulting in elevated endoplasmic reticulum stress and a higher apoptotic rate . These data suggest that the autophagy‐lysosome pathway, involved in the intracellular protein quality control by removing large misfolded proteins and proteins aggregates, is activated in liver cells expressing hFIX‐Fc fusion proteins . This hypothesis is in accordance with the propensity of Fc fusion proteins to form protein aggregates, which is mostly induced by hydrophobic interactions .…”
Section: Discussionmentioning
confidence: 96%
“…Structural modeling platforms, such as the Integrated Modelling Platform (IMP), rely on homology modeling in combination with structural restraints obtained from various techniques [106]. These hybrid modeling approaches incorporate information from a myriad of techniques such as electron microscopy, small angle X-ray scattering, crosslinking, chemical labeling, and hydroxyl footprinting [67, 107109]. Amide accessibility obtained from HDX provides an additional level of information for structural modeling as it can differentiate regions of stable secondary structure from unfolded regions.…”
Section: Introductionmentioning
confidence: 99%
“…The deuterium uptake information can be improved to the single-residue level by using subtraction of deuterium uptake from overlapping peptides or the low-energy dissociation methods, , e.g., ETD or ECD. HDX-MS reports on the hydrogen bonding and solvent accessibility of the protein backbone amide hydrogens and is sensitive to protein structural changes caused by different perturbations. Most importantly, key insights into the protein–protein interactions can be obtained by comparing HDX profiles to map the interfaces for the mAb reversible self-association , and pinpoint the regions with structural changes induced by aggregation. , Understanding protein aggregation at the molecular level could lead to rational design strategies for reducing mAb aggregation during product design, development, and manufacturing.…”
mentioning
confidence: 99%
“…26−28 Most importantly, key insights into the protein−protein interactions can be obtained by comparing HDX profiles to map the interfaces for the mAb reversible self-association 29,30 and pinpoint the regions with structural changes induced by aggregation. 31,32 Understanding protein aggregation at the molecular level could lead to rational design strategies for reducing mAb aggregation during product design, development, and manufacturing. In this study, our focus was on how dimers of an IgG2 mAb (mAb2) formed under two different conditions: (1) during long-term storage under the recommended storage condition and (2) during short-term exposure to a high-temperature thermal stress.…”
mentioning
confidence: 99%